Semi-analytic galaxies-I. synthesis of environmental and star-forming regulation mechanisms - Cora, Sofia Alejandra (2018)
We present results from the semi-analytic model of galaxy formation SAG applied on the MULTIDARK simulation MDPL2. SAG features an updated supernova (SN) feedback scheme and a robust modelling of the environmental effects on satellite galaxies. This incorporates a gradual starvation of the hot gas halo driven by the action of ram pressure stripping (RPS), that can affect the cold gas disc, and tidal stripping (TS), which can act on all baryonic components. Galaxy orbits of orphan satellites are integrated providing adequate positions and velocities for the estimation of RPS and TS. The star formation history and stellar mass assembly of galaxies are sensitive to the redshift dependence implemented in the SN feedback model. We discuss a variant of our model that allows to reconcile the predicted star formation rate density at z ≳ 3 with the observed one, at the expense of an excess in the faint end of the stellar mass function at z= 2. The fractions of passive galaxies as a function of stellar mass, halo mass, and the halo-centric distances are consistent with observational measurements. The model also reproduces the evolution of the main sequence of star-forming central and satellite galaxies. The similarity between them is a result of the gradual starvation of the hot gas halo suffered by satellites, in which RPS plays a dominant role. RPS of the cold gas does not affect the fraction of quenched satellites but it contributes to reach the right atomic hydrogen gas content for more massive satellites (M* ≳10 10 M ⊙ ).